The Village Head Performance in Village Physical Development (Study in Renah Panjang Village, Lubuk Sandi District, Seluma Regency). - Ririn Andita Sari; Antonio Imanda; Yusuarsono Yusuarsono; Bando Amin C. Kader (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
The aim of the study was to determine the Village Head's Performance in the village Physical Development (Study in Renah Panjang Village, Lubuk Sandi Sub-District, Seluma Regency). The method used in this study was descriptive qualitative research. Furthermore, data collection techniques were carried out by means of in- depth interviews, observation and documentation. After the research results were obtained, they were analyzed by means of data reduction, data presentation and drawing conclusions. There were 5 informants in this study consisting of 2 key informants and 3 main informants. This study uses the theory according to performance according to Wibowo (2009: 376) in his book as follows: Attitude Approach in planning village physical development with the coordination of village heads, village officials, BPD members and village community leaders are involved with the results of joint deliberations to determine the implementation development in the village. Even though not all of the community was involved, those who still had a close relationship with the village head were invited to hold discussions. Those who disagree or agree are not involved at all. Behavioral Approach in terms of the information provided by the village head regarding the disbursement of the Village Fund, it was not transparent to the community, only village officials knew when the disbursement of the funds was disbursed. Whereas the community only found out or were informed when there was a deliberation on the planning and implementation of the village's physical development, and even then, the village head who was present, such as community leaders and BPD members, was invited. The Hasi Approach there are some members of the community, such as village officials, community leaders, and BPD members who are involved in the process of planning and implementing village physical development. Meanwhile, some communities are not involved in the process of planning and implementing village physical development directly because there is a lack of closeness with the village head and village officials. The Human Resources Contingency Approach in village officials is still lacking in serving the needs of the community because the average education of high school graduates and Package C school, no one graduated from D3 or S1. Mastery of technology such as computers or laptops, most village officials cannot use or operate, except the village secretary.